Case Report: Resuscitation in Intraoperative Third Space Loss in Pediatric Patient with Paracentesis for Massive Ascites - Astrid; Kapuangan, Christopher (Writing Center IMERI FMUI, 2024)
The accuracy of intraoperative fluid resuscitation is one of the important factors influencing the outcome of surgery. In action conditions with the occurrence of fluid loss from massive